In vitro effect of 470 nm LED (Light Emitting Diode) in keloid fibroblasts - Bonatti,Silvilena (2011)
Purpose: To quantify keloid fibroblasts after irradiation with 470nm blue LED, in vitro. Methods: Fibroblasts from keloid and adjacent skin have been obtained from 6 patients. Cells have been cultivated and maintained in DMEM culture medium. In Petri dishes, they were irradiated with energy doses of 6J, 12J and 18J. After 24 h, counting was done by the average of the triplicates for each sample. Results: There were no significant differences in the number of irradiated keloid fibroblasts at the studied doses (p=0.261). In adjacent skin fibroblasts, differences were observed (p=0.025) concerning the doses of 18 J and 6 J (p=0.03). Conclusions: There was a reduction in the number of adjacent skin fibroblasts irradiated with 470nm blue LED at the energy dose of 18 J compared to the ones irradiated at the energy dose of 6 J. There were no changes in keloid fibroblasts counting at any of the doses applied, 24 h after irradiation.